PENERAPAN MODEL PENGAJARAN LANGSUNG DENGAN ASSESSMENT PROJECT WORK SEBAGAI UPAYA PENINGKATAN MOTIVASI DAN HASIL BELAJAR MENGGAMBAR KELAS XI SMKN 3 SENDAWAR KUTAI BARAT - Logan, Nasius; Kusnan, Kusnan; Winanti, E. Titiek (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
ABSTRACT This research aims to find the improvement of the students' motivation, study result and learning activities in the drawing materials of door frame, door, and wood window after the students are given the direct leaming model by using Project Work Assessment to improve students' drawing motivation and study result at eleventh grade of SMK Negeri 3 Sendawar Kutai Barat. The research in this thesis uses classroom action research by using descriptive quantitative analysis in two cycles. There are 12 students of eleventh grade become the subject of the research. The instruments used to collect the data are questionnaire for students' learning motivation, project assessment, and observation sheet for students' activities. The results of the research are: (1) the students' learning motivation is 75% in the first cycle and it becomes 91.67% in the second cycle; (2) the students; learning result in their spiritual attitude is in a good category. It is 53.33% in the first cycle and it becomes 83.33% in the second cycle. the students' social aspect is in good category. It is 66.67% in the first cycle and it becomes 91.67% in the second cycle. The classical achievement in the skill aspect is 66.67% in the first cycle and it becomes 91.67% in the second cycle; (3) The improvement of the students' leaming activities is in the category of the most dominant. The students do the drawing assignment for 87.50% in the first cycle and it becomes 97.92% in the second cycles. The minimal activity which is conducted by the students is asking the questions to the teacher. It is 20.83% in the first cycle and it becomes 37.50% in the second cycle. Keywords: Building Construction Drawing, Motivation, Activities, Study Result.